Expectations, Infections, and Economic Activity - Eichenbaum, Martin; Godinho de Matos, Miguel; Lima, Francisco; Rebelo, Sergio; Trabandt, Mathias (Journal of Political Economy, 2024)
This paper develops a quantitative theory of how people weigh the risks of infections against the benefits of engaging in social interactions that contribute to the spread of infectious diseases. Our framework takes into account the effects of public policies and private behavior on the spread of the disease. We evaluate the model using a novel micro panel dataset on consumption expenditures of young and older people across the first three waves of COVID-19 in Portugal. Our model highlights the critical role of expectations in shaping how human behavior influences the dynamics of epidemics.